(3fXQjGJ GdGJUGd h GdGYdGe GdLeGgjQj (B/s - (3GdVdGYjf, fVGd adGMs; (3Ydj adGM GdVdGYjf(B;(3cGaj, eUWai jhSa (B;(3h GNQhfs ((3YeGf (B:s (3OGQ GdGYUGQ GdYdej ddfTQ h GdJhRjY ,s, 2016)
(3JWhQ fXQjGJ GdGJUGd(B: (3HPdJ YOI eMGhdGJ YdejI dJMdjd YedjI GdGJUGd hhUa GHYGOgG hYfGUQgG, heG jgefG GdJCcjO Ydjg ai MOhO gPg GdOQGSI C GZdH (B- (3Gf de fbd LejY (B- (3GdOQGSGJ GdJi JfGhdJ ehVhY GdGJUGd GdLeGgjQi CcOJ Ydi GgejI GdhSjdI GdGJUGdjI hOhQgG GdeDKQ hGdQFjSi ai YedjI GdGJUGd GdLeGgjQjI(B. (3hai gPG GdUOO jecf Cf fTjQ Gdi fehPL (B((3OjajO HQdh(B) (3GdPi jQi Gf gfGc GQHYI YfGUQ Jchf GdYedjI GdGJUGdjI hJTed(B: (3GdeQSd h GdQSGdI h GdhSjdI h GdeSJbHd(B. (3hef GdfeGPL GdegeI GdJi GSgeJ ai HfGA fXQjGJ GdGJUGd GdfehPL GdPi bOeg (B((3hdHQ TQGe(B) (3ai YGe (B1974(3e hWhQg i YGe (B1971(3e hai gPG GdfehPL jbO TQGe GdYfGUQ GdGSGSjI Ydi GdfMh GdJGdi(B: (3C(B- (3GdeUOQ Ch UGMH GdacQI(B. (3H(B- (3GdJYHjQ Yf GdacQI hhVYgG ai TaQI hUjGZJgG ai QehR dJchjf GdQSGdI(B. (3J(B- (3GdeSJbHd GdPi jJdbi GdQSGdI hjac QehRgG(B. (3K(B- (3GdGSJLGHI Gh GdgOa hQLY GdUOi GdPi bO jUd Gh dG jUd Edi GdeQSd Gh UGMH GdacQI(B. (3hjYJeO TQGe ai gPG GdfehPL Ydi CacGQ GdHGMKjf TGfhf h hjaQ , hNGUI ajeG jJYdb HQLY GdUOi hGdJThjT , hjVja ef NdGd fehPLg GdfXGe GdhXjai dYedjI GdGJUGd ceG bOe ef NdGd gPG GdfehPL eaGgje egeI eKd GdGWGQ GdOdGdi hGdNHQI GdeTJQcI hGgejJgG ai YedjI GdGJUGd hGdi Pdc fLO Gf GdeDQN hGdcGJH GdGfLdjRi hjdR jHjf Gf GdJGQjN GdGfSGfi gh XGgQI GLJeGYjI hGMOI JOaY HGdGfSGf Gdi GdGJUGd HCNjg GdGfSGf, ai ecGf BNQ Gh eLJeY BNQ, hgh HPdc jfXQ Edi bUI GdJWhQ GdJGQjNi GdHTQi Ydi CfgG bUI JWhQ YedjI GdEJUGd , hjbSegG Edi NeS eQGMd hgi(B: (3GdcdGe, GdcJGHI, GNJQGY GdWHGYI, GdeQMdI GdYGdejI, hCNjQG eQMdI GdEPGYI hGdGJUGd GdEdcJQhfi, hai gPg GdeQMdI GdCNjQI dJWhQ GdGJUGd CUHM ddhSGFd GdEdcJQhfjI OhQG egeG ai MjGI GdeLJeY, hGSJWGY GdGfSGf fbd GacGQg heTGYQg heYdheGJg YHQ GdMhGLR GdLZQGajI GdeMOhOI HESJNOGe GLgRI GdePjGY Ke GdJdjaRjhf hCNjQG THcI GdGfJQfJ(B.s
(3HHdjhZQGajI U(B. 251-254s
Keywords: (3GdEYdGes; (3GdEYdGe GdLeGgjQjs; (3fXQjGJ GdGJUGd s